PENGGUNAAN METODE SIMULASI UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS III SDN 015 PAGARAN TAPAH DARUSSALAM - Aminah, Siti (Aksara Public, 2017)
This research is motivated by the lack of Student Learning Outcomes Civics Class III SDN 015 Pagaran Tapah Darussalam Goals to be achieved in this research is to improve Student Learning Outcomes Civics Class III SDN 015 Pagaran Tapah Darussalam through the application of simulation methods were implemented during the first month. This research was conducted in SDN 015 Pagaran Tapah Darussalam. Classes are meticulous researchers are Class III by the number of students as many as 21 people. Based on the analysis and discussion as described in chapter IV can be concluded that the use of simulation methods to improve learning outcomes SDN 022 class III Teratak reed Siak Hulu subdistrict. This success is due to the use of simulation methods become more active student activities which means that students tend to be positive in following the teaching-learning process given by the teacher. Under these conditions, the enrollment rate will increase and in turn can increase the yield beajar siswanya.sebagaimana in cycle one students' learning outcomes only achieve mastery of grade 76.2% and increased to 84.9% with students yangbelum reached above 70 only one student or 4.7%, the study showed dnegan so successful that the simulation method Civics students improve learning outcomes.